2020
DOI: 10.35609/jmmr.2020.5.1(8)
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Customer Relationship Management (CRM) Indicators on Customer Loyalty of Sharia Based Banking System

Abstract: Objective – The purpose of this research is to determine whether CRM (Customer Relationship Management) indicators, namely complaint resolution, customer orientation, customer empowerment and customer knowledge affect the loyalty of sharia bank customers in North Sumatra. Methodology/Technique – The sample of this study is 120 Islamic banking customers in North Sumatra, namely customers at PT. BNI Syariah Tbk, PT. Bank Syariah Mandiri Tbk and PT. BRI Syariah Tbk. The analytical method used is multiple linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
0
13
1
3
Order By: Relevance
“…The results of this study are not in line with research conducted by Nieves & Quintana, (2018) which found that customer orientation has a positive and insignificant effect on corporate performance in companies engaged in finance. In addition to this research, research conducted by Lubis et al, (2019) found results that contradict this research that there is an influence between customer orientation and corporate performance. Customer orientation is a type of orientation where consumer needs become the basis for an organization to plan and design its strategy (Valentine, 2015).…”
Section: Discussioncontrasting
confidence: 54%
“…The results of this study are not in line with research conducted by Nieves & Quintana, (2018) which found that customer orientation has a positive and insignificant effect on corporate performance in companies engaged in finance. In addition to this research, research conducted by Lubis et al, (2019) found results that contradict this research that there is an influence between customer orientation and corporate performance. Customer orientation is a type of orientation where consumer needs become the basis for an organization to plan and design its strategy (Valentine, 2015).…”
Section: Discussioncontrasting
confidence: 54%
“…It is an association with gender for the group of professionals and self-employed without employees and temporary employees, with men reporting that they are happier than women. For the eventual employees, with women happier than men [88], the hypothesis H 1EmpSex is supported, but only for entrepreneurs without employees [89].…”
Section: Discussionmentioning
confidence: 89%
“…Scholars (e.g. Lubis et al 2020;Quddoos et al 2021) have widely argued that affective commitment is a critical factor to enhance the overall loyalty intention of customers in multiple settings and should be more intensively explored in studies that investigate the commitment-loyalty link. Therefore, although the business sector needs to develop an understanding of the factors that positively influence affective commitment in a B2C environment (customer orientation and perceived value), it must also understand that affective commitment remains crucial in the strengthening of future loyalty intentions.…”
Section: A Perspective On Affective Commitment In Strengthening Custo...mentioning
confidence: 99%